The Comparison of ISO 14001 Implementation in Indonesia Construction Companies (Case Study: PT. Waskita Karya Tbk, PT. Wijaya Karya Tbk, PT. PP (Persero) Tbk) - Filson Maratur Sidjabat; Putri Annisa Febrian (President University, 2020)
Growing the economy is a concern for President Joko Widodo's (Jokowi) government, which is why attention is so important to the construction companies. Some of the largest construction firms reported major rises throughout the value of federal contracts. Attempts to improve the infrastructure services of the organization can be made through a control system of factors affecting the performance of the company which ultimately determines the business success in achieving its goals. PT. Waskita Karya Tbk and PT. Wijaya Karya Tbk implement green construction, and green building for their environmental management quality standard, meanwhile PT PP (Persero) implement 3R (Reduce, Reuse, Recycle) theory. Regarding raw materials / products which come mainly from nature. Those three businesses have received no reports over the course of the year about the environmental business. The environmental management system then proves that improve the management standard will increase productivity and decrease the risk.